Professional Development of Indonesian Librarians: towards Digital Library Environment - Zulfikar Zen (AT-TA'LIM, 2014)
Libraries are an information institution. Nowadays, the information are available in printed, recorded, and online formats. The librarians have to adapt themselves with the latest development, especially with the digitalÂ  environment. Some libraries in Indonesia have been provided with digital formats such as e-books, e-journals, and other internet facilities. The library institutions, library schools, and library professional associations in Indonesia have also been involved with the digital environment, resulting in the improvement of their knowledge and skills.